2020
DOI: 10.1155/2020/8813285
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Tainan 9 Peanut Seed Storability and Germination under Low Temperature

Abstract: Low temperature condition during December to January can limit seed emergence and seedling establishment for peanut production in Thailand. The objective of this study was to determine the effects of peanut seed priming on seed germination and vigor under optimal and low temperature conditions before and after 9 months of storage. Tainan 9 peanut seeds were primed with salicylic acid (SA), ascorbate (ASA), CaCl2, or chitosan and tested for germination at 25°C (optimal temperature) and 15°C (low temperature) be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Wondimu et al (2018 showed that the highest seed germination%, seedling dry weight seedling length, seedling vigor index were recorded when seed soaking in ZnSO4 and hydro-primin over the unprimed sorghum seeds. Jeammuangpuk et al (2020) found that seed soaking for in 50 mgL −1 of SA before germinating encouraged seed germination when compared to un-soaked seeds. Harris et al (2000) showed that soaking seed in water on the farm significantly improved establishment and viability of chickpea and maize, caused in faster growth, early flowering and maturation and higher yields.…”
Section: Resultsmentioning
confidence: 97%
“…Wondimu et al (2018 showed that the highest seed germination%, seedling dry weight seedling length, seedling vigor index were recorded when seed soaking in ZnSO4 and hydro-primin over the unprimed sorghum seeds. Jeammuangpuk et al (2020) found that seed soaking for in 50 mgL −1 of SA before germinating encouraged seed germination when compared to un-soaked seeds. Harris et al (2000) showed that soaking seed in water on the farm significantly improved establishment and viability of chickpea and maize, caused in faster growth, early flowering and maturation and higher yields.…”
Section: Resultsmentioning
confidence: 97%
“…There are various approaches to seed priming such as hydropriming, halopriming, osmopriming, hormoprimimg, biopriming, thermopriming, and solid matrix priming [ [25] , [26] , [27] , [28] , [29] , [30] ]. The consequences of priming are influenced by the priming agent, the duration of priming, and the dosage of priming agents [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The germination status of peanuts soaked in SA and ASA was observed at 25 °C and 15 °C. At 15 °C, the germination ratios of peanuts soaked in SA and ASA were 97% and 98%, respectively, while the germination ratio of the control group was only 86% [ 19 ].…”
Section: Introductionmentioning
confidence: 99%